2011
DOI: 10.1177/0022034511423399
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Story of Mammalian-specific Amelogenin Exons 4, “4b”, 8, and 9

Abstract: Amelogenin gene organization varies from 6 exons (1,2,3,5,6,7) in amphibians and sauropsids to 10 in rodents. The additional exons are exons 4, 8, 9, and "4b", the latter being as yet unidentified in AMELX transcripts. To learn more about the evolutionary origin of these exons, we used an in silico approach to find them in 39 tetrapod genomes. AMEL organization with 6 exons was the ancestral condition. Exon 4 was created in an ancestral therian (marsupials + placentals), then exon 9 in an ancestral placental, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The 6 affected persons had this sequence variation, and none of the 7 unaffected persons had it. This nucleotide change was well conserved in all species except for the opossum (Sire et al, 2012). Further sequencing of the other AI-related genes did not identify any disease-causing mutations.…”
Section: Identification Of a Silent Mutation In The Amelx Genementioning
confidence: 88%
“…The 6 affected persons had this sequence variation, and none of the 7 unaffected persons had it. This nucleotide change was well conserved in all species except for the opossum (Sire et al, 2012). Further sequencing of the other AI-related genes did not identify any disease-causing mutations.…”
Section: Identification Of a Silent Mutation In The Amelx Genementioning
confidence: 88%
“…Further studies of amelogenin in lower chordates are necessary to better understand the evolution of these exons. Another novel exon found between so-called exon 5 and 6 in a reptile, Ctenosaura similis 20) , and in mammals, newly exon 4b and 8 in AMELX have found as a result of duplication of so-called exon 4 and 5 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Amelogenin exon4 is present in the amelogenin gene of many species (Sire et al 2012), and amelogenin proteins that contain exon4-encoded proteins have been reported in mouse (Simmer 1994) and porcine (Yamakoshi 2011) enamel matrix. Messenger RNAs (mRNAs) containing exon4 have been amplified from human (Salido et al 1992), mouse (Hu et al 1997), and rat (Li et al 1995) enamel organs.…”
Section: Introductionmentioning
confidence: 99%